KOMPUTASI KERUGIAN LINTASAN SINYAL DENGAN MODEL HATA - Suhartono, Suhartono (MATEMATIKA, 2009)
Signal is a wave that can be expressed by physical phenomenon. Mathematically signal wave can be represented as a function of single or many independent variables, for example signal wave over building as a function of distance or time. In fact, signal spreading as a wave have many attenuation, for example is caused by difraction when the signal over the urban area or building. The purpose of the research is to present the signal path loss model in the urban area by using Hata model. The result of the computation has shown that the decreasing of the signal path loss in urban area can be effected by the increasing of the receiver antenna height.